2019
DOI: 10.5604/01.3001.0013.1482
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions following low anterior resection of the rectum in rectal cancer patients

Abstract: Introduction. Low anterior resection of the rectum (LAR) is a treatment of choice in patients with diagnosed low rectal cancer. Rectal cancer surgery has a close relationship with the urinary-sexual organs and also with related nerves and nerve plexus. Thus, the sympathetic and parasympathetic nerves of the pelvic area may be damaged. As a result of this, the important point is the sexual function loss following rectal surgeries. The aim of the study was to investigate the sexual disorders in patients with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Normally distributed variables were analysed using t -test and ANOVA, whereas non-normally distributed variables were analysed using the Mann–Whitney U test and Kruskal–Wallis test. The key indicators obtained using univariate analysis and other recognised risk factors related to LARS (such as radiotherapy, tumour location, body mass index [BMI] and stoma [ 2 , [21] , [22] , [23] , [24] , [25] , [26] ]) were subjected to generalised estimating equation. A p-value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Normally distributed variables were analysed using t -test and ANOVA, whereas non-normally distributed variables were analysed using the Mann–Whitney U test and Kruskal–Wallis test. The key indicators obtained using univariate analysis and other recognised risk factors related to LARS (such as radiotherapy, tumour location, body mass index [BMI] and stoma [ 2 , [21] , [22] , [23] , [24] , [25] , [26] ]) were subjected to generalised estimating equation. A p-value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that bowel dysfunction is associated with a lack of sexual desire, sexual inactivity and sexual dissatisfaction. Specifically, faecal incontinence has a significant impact on sexuality (desire, frequency of intercourse, reaching orgasm and satisfaction with hugging and kissing) [110,141,145] (2b). In a case-control study, CRC survivors with ostomy were more anxious than healthy volunteers, and a low frequency of sexual intercourse was significantly more common in this patient group (68% vs. 30%), with 54% avoiding intercourse compared with 4% among controls [146] (3b).…”
Section: Urinary Dysfunction In Crc Survivors (Figure 6)mentioning
confidence: 99%
“…ED or impotence is defined as the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance and is reported in 11%-93% of CRC survivors [143][144][145][147][148][149][150] (2b), whereas EJD is reported in 19%-68% [144,145,148] (2b).…”
Section: Sexual Dysfunction In Menmentioning
confidence: 99%